2020
DOI: 10.3390/cancers12113304
|View full text |Cite
|
Sign up to set email alerts
|

Novel DNMT3A Germline Variant in a Patient with Multiple Paragangliomas and Papillary Thyroid Carcinoma

Abstract: Over the past few years, next generation technologies have been applied to unravel the genetics of rare inherited diseases, facilitating the discovery of new susceptibility genes. We recently found germline DNMT3A gain-of-function variants in two patients with head and neck paragangliomas causing a characteristic hypermethylated DNA profile. Here, whole-exome sequencing identifies a novel germline DNMT3A variant (p.Gly332Arg) in a patient with bilateral carotid paragangliomas, papillary thyroid carcinoma and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In particular, its PWWP domain recognizes histone H3K36 di-and tri-methylation (H3K36me2/3), which facilitates targeting to gene bodies and promoter-proximal intergenic regions of highly expressed genes (27)(28)(29)(30)(31). Missense mutations that disrupt the DNMT3A PWWP-H3K36me2/3 interaction have been reported in patients with Heyn-Sproul-Jackson syndrome or rare neuroendocrine tumors (32)(33)(34). Interestingly, cells harboring DNMT3A PWWP mutations showed increased DNMT3A1 localization and DNA hypermethylation at promoter CGIs of Polycomb target genes (32,(35)(36)(37).…”
Section: This Histone Post-translational Modification (Ptm) Is Establ...mentioning
confidence: 99%
“…In particular, its PWWP domain recognizes histone H3K36 di-and tri-methylation (H3K36me2/3), which facilitates targeting to gene bodies and promoter-proximal intergenic regions of highly expressed genes (27)(28)(29)(30)(31). Missense mutations that disrupt the DNMT3A PWWP-H3K36me2/3 interaction have been reported in patients with Heyn-Sproul-Jackson syndrome or rare neuroendocrine tumors (32)(33)(34). Interestingly, cells harboring DNMT3A PWWP mutations showed increased DNMT3A1 localization and DNA hypermethylation at promoter CGIs of Polycomb target genes (32,(35)(36)(37).…”
Section: This Histone Post-translational Modification (Ptm) Is Establ...mentioning
confidence: 99%
“…A second study confirmed the role of DNMT3A in the susceptibility to develop H&N PGL ( Table 1 ). The patient presented with multiple clinical features, a finding that suggested a heterogeneous phenotypic spectrum related to DNMT3A germline variants ( Mellid et al 2020 ).…”
Section: The Pgl Genetic Testing In Routine Practice Changes the Pati...mentioning
confidence: 99%
“…DNA methylation patterns provide a paradigm for the epigenetic inheritance of cancer susceptibility, with emphasis on co-methylated networks [ 9 ]. Multiple paragangliomas and papillary thyroid carcinoma are likely connected to mutations in the DNMT3a gene, responsible for de novo methylation [ 10 ]…”
mentioning
confidence: 99%
“…DNA methylation patterns provide a paradigm for the epigenetic inheritance of cancer susceptibility, with emphasis on co-methylated networks [9]. Multiple paragangliomas and papillary thyroid carcinoma are likely connected to mutations in the DNMT3a gene, responsible for de novo methylation [10] Changes in developmental programs do not necessarily involve DNA or RNA. The widespread Alzheimer's disease is connected to the accumulation of misfolded polymerized proteins, amyloid β (Aβ) and tau, in brains, and to neuronal degeneration, dementia, and death.…”
mentioning
confidence: 99%